Electronic dental record-based surveillance of non-communicable conditions. (April 2021) - Elangovan, S.; Xie, X.J.; McBrearty, C.; Caplan, D.J.
Abstract: Objective: The objective of the study is to demonstrate that electronic dental records (EDRs) can be used to mine meaningful public health information. Study design: Retrospective electronic dental chart-based reporting of disease prevalence. Methods: Using dental EDRs (N = 104, 768), the authors assessed the prevalence of common non-communicable medical conditions among unique patients seen at a United States (U.S.) dental college. Results: The prevalence of following conditions in patients visiting a U.S. dental college increased steadily with increasing age: hypertension, angina, stroke, myocardial infarction, congestive heart failure, diabetes, cancer, kidney disease, thyroid disease, and allergies. Prevalence of these conditions was several-fold higher in the 66+ years group than among younger adults. Prevalence of many of the assessed conditions approximated published national estimates. Conclusions: In addition to the indispensable use of EDRs in dental education and patient management, EDRs can be mined to report on prevalence of non-communicable medical conditions among patients/population receiving dental care. Completeness and accuracy of entered information will significantly improve the usefulness of EDR for disease surveillance and research applications.